Retrosynthetic Analysis of Penidaleodiolide A with Relevance to Epilepsy Therapy - Kim, Eunri; Lim, Joseph (Technium BioChemMed, 2025)
Penidaleodiolide A, a recently discovered cage-like polyketide isolated from Penicillium daleae L3SO in association with Monotropa uniflora, has demonstrated selective and reversible inhibition of hippocampal basket neuron excitability without cytotoxicity. This unique activity highlights its promise as a novel therapeutic scaffold for drug-resistant epilepsy and other hyperexcitability-related neurological disorders. However, reliance on natural extraction from scarce fungal sources poses limitations in yield and accessibility. To address this, our study presents a retrosynthetic pathway for the laboratory synthesis of penidaleodiolide A. Through oxidation-level analysis, strategic 1,3- and 1,5-disconnections, and retro-aldol and Claisen-type fragmentations, we deconstructed the complex tricyclic scaffold into simpler and commercially available precursors, including glycolic acid, propanal, and β-hydroxybutyric acid. This systematic approach underscores the feasibility of reconstructing the molecule synthetically, offering flexibility and scalability compared to biosynthetic routes. By bridging natural product chemistry with retrosynthetic design, this work lays a foundation for future synthetic efforts toward penidaleodiolide A and supports its further pharmacological exploration as a safer, more effective treatment for neurological disorders.